Worried, weary and worn out: mixed-method study of stress and well-being in final-year medical students. Issue 12 (10th December 2020) - Lane, Abbie; McGrath, Jack; Cleary, Eimear; Guerandel, Allys; Malone, Kevin M
Abstract : Objective: Although there is much focus on burnout and psychological distress among doctors, studies about stress and well-being in medical students are limited but could inform early intervention and prevention strategies. Design: The primary aim of this mixed-method, cross-sectional survey was to compare objective and subjective levels of stress in final-year medical students (2017) and to explore their perspectives on the factors they considered relevant to their well-being. Setting: University College Dublin, the largest university in Ireland. Participants: 161 of 235 medical students participated in this study (response rate 69%). Results: 65.2% of students scored over accepted norms for the Perceived Stress Scale (34.8% low, 55.9% moderate and 9.3% high). 35% scored low, 28.7% moderate and 36.3% high on the Subjective Stress Scale. Thematic analysis identified worry about exams, relationships, concern about the future, work–life balance and finance; one in three students reported worry, irritability and hostility; many felt worn out. Cognitive impacts included overthinking, poor concentration, sense of failure, hopelessness and procrastination. Almost a third reported sleep and appetite disturbance, fatigue and weariness. A quarter reported a 'positive reaction' to stress. Positive strategies to manage stress included connection and talking, exercise, non-study activity and meditation. Unhelpful strategies included isolation and substance use. No student reported using the college support services or sought professional help. Conclusion: Medical students experience high levels of psychological distress, similar to their more senior doctor colleagues. They are disinclined to avail of traditional college help services. Toxic effects of stress may impact their cognition, learning, engagement and empathy and may increase patient risk and adverse outcomes. The focus of well-being in doctors should be extended upstream and embedded in the curriculum where it could prevent future burnout, improve retention to the profession and deliver better outcomes for patients.